Evaluating the impact of AI on the critical thinking skills among the higher education students by combining the TAM model and critical thinking theory - Ninghardjanti, Patni; Umam, Muhammad Choerul; Subarno, Anton; Winarno, Winarno; Langgi, Novedi Risanti; Widodo, Jumiyanto (Frontiers in Education, 2025)
The following research analyzes the relation between the utilization of Artificial Intelligence (AI) tools among university students and their relation with critical thinking skills by combining the Technology Acceptance Model (TAM) model and critical thinking theory. This research introduced the Metacognitive TAM (Meta-TAM) integrated with the Information Systems (IS) Success model as a theoretical innovation. The current research was carried out with a quantitative method approach, with 200 respondents from the Office Administration Education Department, Universitas Sebelas Maret, Indonesia. The research data were analyzed using the SEM with SmartPLS 4.0 software. The key constructs of attitude toward use (ATU), motivation to use (MTU), perceived usefulness (PU), perceived ease of use (PEOU), and behavioral intention (BI) were analyzed to assess the primary factors that influence the adoption of the AI-based tools. The findings emphasize that the TAM constructs significantly influenced behavioral intention, whereas critical thinking played a crucial mediating role. The strongest path was observed from attitude toward use to behavioral intention (β = 0.737), which emphasizes the importance of affective and evaluative assessment in students' decision-making. Then, it can be concluded that not only the usability or utility, but also students' strategic thinking, epistemic vigilance, and intellectual autonomy have a significant impact on the AI adoption among higher education students. This study offers practical implications for AI-integrated curriculum design and ethical technology implementation in learning environments. This research contributes a novel perspective to educational technology literature and encourages future cross-cultural, longitudinal studies that examine AI's cognitive impact while safeguarding critical thinking development in diverse academic contexts.